CREATIVITY IS THE FACE OF OUR NATIONAL SPIRITUALITY - Quchqarov Bahodir Ulmasovich; Urinbayev Isroiljon Kadirjonovich (Journals Park Publishing, 2024)
In our country descriptive art and practical art being given attention and that's it creates possibilities Our country in HEIs this direction students productive using big creative and scientific to achievements achieve coming about data is given
Keywords: Descriptive art, Art education, culture, painting, education, light-shadow, creativity, artist, color.